2022
DOI: 10.1111/ane.13670
|View full text |Cite
|
Sign up to set email alerts
|

Early post‐traumatic seizures in hospitalized patients with traumatic brain injury

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
4
4
1
Order By: Relevance
“…In this study, alcohol abuse is a strong predictor of early PTS. This is consistent with studies from Norway [ 17 ], Southern Thailand [ 7 ], and the USA [ 14 ] which reported alcoholism as a strong risk factor for early PTS. This may be due to alcohol consumption may decrease seizure threshold by acting on gamma-aminobutyric acid receptors [ 17 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, alcohol abuse is a strong predictor of early PTS. This is consistent with studies from Norway [ 17 ], Southern Thailand [ 7 ], and the USA [ 14 ] which reported alcoholism as a strong risk factor for early PTS. This may be due to alcohol consumption may decrease seizure threshold by acting on gamma-aminobutyric acid receptors [ 17 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study indicates that there is a high incidence of early PTS, which was observed in 17.7% of patients with moderate or severe TBI. This finding was higher than the report of previous studies conducted in the United States (1.9%) [ 16 ], Australia (2.7%) [ 9 ], Thailand (5.6%) [ 7 ], Italy (7%) [ 2 ], Shenzhen, China (2.8%) [ 18 ] and Norway (5.6%) [ 17 ], New Delhi, India(2.1%) [ 19 ], and Nigeria(10.1%) [ 21 ]. Likewise, a recent study based on a nationwide trauma database in the USA found that early seizures occurred in 0.4% of patients with TBI [ 14 ].…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…2 Risk factors for early PTS include TBI severity, prior medical comorbidities, presence of subdural or subarachnoid hemorrhage, and alcohol abuse. [2][3][4] Early PTS are associated with poor long-term functional outcomes, late PTS and increased mortality. 3 The 2017 Brain Trauma Foundation's Guidelines for the Management of Severe TBI recommend the use of anticonvulsant prophylaxis (ACP) with phenytoin for the first 7 days post-injury to decrease the incidence of early PTS when the overall benefit is thought to outweigh the risk of complications.…”
Section: Introductionmentioning
confidence: 99%